Effect of Optometric Multisensory Training (OMST) on a Patient with Post-Concussive Visual Snow Syndrome. - Habermehl, Bradley E.; Yadav, Naveen K. (Optometry & Visual Performance, 2026)
Background: Optometric Multisensory Training (OMST) is a unique method involving the simultaneous presentation of sensory stimulations in a safe and controlled clinical situation. This includes syntonic optometric phototherapy, vestibular (motion) stimulation, and auditory stimulation. The purpose of this study is to evaluate the effectiveness of OMST in improving visual and post-concussive symptoms in a patient diagnosed with post-concussive visual snow syndrome (VSS) following mild traumatic brain injury (mTBI). Case Report: A 57-year-old female with a history of mTBI presented with persistent post-concussion syndrome (PCS), including VSS, oculomotor dysfunction, vestibular disturbances, cognitive deficits, and migraines. The patient underwent a 30-day OMST program consisting of in-office multisensory therapy combined with at-home syntonic phototherapy. Objective eye movement metrics and subjective symptom reports were assessed pre- and post-intervention. Results: Using the RightEye standardized testing protocol, significant improvements were observed in eye movement performance, with overall scores improving from an average of 24 pre-treatment to 61 post-treatment. Using the Brain Injury Vision Symptom Survey (BIVSS), the patient reported an 80% reduction in visual snow symptoms and a 60% reduction in overall PCS symptoms, along with improvements in sleep quality, vestibular function, and cognitive processing. Conclusion: OMST appears to be a promising neuro-optometric rehabilitation approach for patients with post-concussive VSS, demonstrating both objective and subjective clinical improvements.